Interleukin 10 (IL10) proximal promoter polymorphisms beyond clinical response in classical Hodgkin lymphoma: Exploring the basis for the genetic control of the tumor microenvironment - Vera Lozada, Gabriela (2018)
Interleukin-10 (IL10) is an immune regulatory cytokine. Single nucleotide polymorphisms (SNPs) in IL10 promoter have been associated with prognosis in adult classical Hodgkin lymphoma (cHL). We analyzed IL10 SNPs −1082 and −592 in respect of therapy response, gene expression and tumor microenvironment (TME) composition in 98 pediatric patients with cHL. As confirmatory results, we found that −1082AA/AG; −592CC genotypes and ATA haplotype were associated with unfavourable prognosis: Progression-free survival (PFS) was shorter in −1082AA+AG (72.2%) than in GG patients (100%) (P = 0.024), and in −592AA (50%) and AC (74.2%) vs. CC patients (87.0%) (P = 0.009). In multivariate analysis, the −592CC genotype and the ATA haplotype retained prognostic impact (HR: 0.41, 95% CI 0.2–0.86; P = 0.018, and HR: 3.06 95% CI 1.03–9.12; P = 0.044, respectively). Our analysis further led to some new observations, namely: (1) Low IL10 mRNA expression was associated with −1082GG genotype (P = 0.014); (2) IL10 promoter polymorphisms influence TME composition;−1082GG/−592CC carriers showed low numbers of infiltrating cells expressing MAF transcription factor (20 vs. 78 and 49 vs. 108 cells/mm2, respectively; P< 0.05); while ATA haplotype (high expression) associated with high numbers of MAF+ cells (P = 0.005). Specifically, −1082GG patients exhibited low percentages of CD68+MAF+ (M2-like) intratumoral macrophages (15.04% vs. 47.26%, P = 0.017). Considering ours as an independent validation cohort, our results give support to the clinical importance of IL10 polymorphisms in the full spectrum of cHL, and advance the concept of genetic control of microenvironment composition as a basis for susceptibility and therapeutic response.